2020
DOI: 10.1109/jphotov.2019.2947758
|View full text |Cite
|
Sign up to set email alerts
|

KF Postdeposition Treatment in N2 of Single-Stage Thin Cu(In,Ga)Se2 Absorber Layers

Abstract: Thin (<500 nm) single-stage co-evaporated Cu(In, Ga)Se2 (CIGS) absorber layers are treated with a KF post anneal in N2 atmosphere. The conditions of the post anneal, initial acceptor concentration and the temperature are varied. Solar cells are characterized with current-voltage and capacitancevoltage measurements. Efficiencies up to 12% with an open circuit voltage (Voc) of > 640 mV were achieved after KF treatment. From SCAPS simulations and IVT measurements it is concluded that the Voc of these cells are li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…This is something we observed before, and it was found that it depends on the initial doping. [16] Similar small changes are found for the AlO x solar cells compared to the reference. When RbF-PDT is applied on the AlO x passivated solar cells though, we observe a significant decrease in the doping for all solar cells.…”
Section: Cigs Solar Cells Performancesupporting
confidence: 69%
See 1 more Smart Citation
“…This is something we observed before, and it was found that it depends on the initial doping. [16] Similar small changes are found for the AlO x solar cells compared to the reference. When RbF-PDT is applied on the AlO x passivated solar cells though, we observe a significant decrease in the doping for all solar cells.…”
Section: Cigs Solar Cells Performancesupporting
confidence: 69%
“…[12,13] To a lesser extent, alkali treatments have also been investigated in ultrathin CIGS solar cells. [14][15][16] Though alkali treatments have led to record efficiencies, not all solar cell parameters are always improved and losses in the fill factor (FF) are often observed. [17][18][19][20][21][22][23] Temperature-dependent currentvoltage ( J-V) measurements show that this may be caused by an injection barrier.…”
Section: Introductionmentioning
confidence: 99%
“…45 The 3 -stage co-evaporation lead to a small in depth Ga The process was done by spin coating followed at room temperature with a 0.2 Molarity of KF followed by an anneal in N2 atmosphere at 613.15 K more details in. 42 The substrates were finalized all with the same process conditions, with the final architecture being CIGS/CdS/i-ZnO/ZnO:Al/Ni-Al-Ni 46 . 12 solar cells were made for each type of devices with an area of 0.5 cm 2 defined by mechanical scribing.…”
Section: Methodsmentioning
confidence: 99%
“…After the CIGS growth, a KF-PDT was applied to PassKF and DoublePass. The process was done employing the optimized conditions by de Wild et al, , by spin coating 0.2 M of KF at room temperature (RT) followed by annealing in a N 2 atmosphere at 613.15 K. The devices were finalized with the deposition of a stack of CdS/i-ZnO/ZnO:Al/Ni-Al-Ni, with the same process conditions as described elsewhere . Twelve solar cells were made for each type of devices with an area of 0.5 cm 2 defined by mechanical scribing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation